2013
DOI: 10.1016/j.abb.2013.08.014
|View full text |Cite
|
Sign up to set email alerts
|

UDP-galactopyranose mutases from Leishmania species that cause visceral and cutaneous leishmaniasis

Abstract: Leishmaniasis is a vector-borne, neglected tropical disease caused by parasites from the genus Leishmania. Galactofuranose (Galf) is found on the cell surface of Leishmania parasites and is important for virulence. The flavoenzyme that catalyzes the isomerization of UDP-galactopyranose to UDP-Galf, UDP-galactopyranose mutase (UGM), is a validated drug target in protozoan parasites. UGMs from L. mexicana and L. infantum were recombinantly expressed, purified, and characterized. The isolated enzymes contained ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…However, it was later determined that UGM is only active when the flavin is in the reduced form (Zhang and Liu, 2000;Sanders et al, 2001;Goni et al, 2008;Oppenheimer et al, 2010Oppenheimer et al, , 2011Maaliki et al, 2020). Eukaryotic UGMs from A. fumigatus and the protozoa T. cruzi, L. Mexicana, and L. infantum utilize NADPH as a co-substrate and can both reinstate and stabilize the reduced form of the enzyme under aerobic conditions (Dhatwalia et al, 2012c;Oppenheimer et al, 2012;Fonseca et al, 2013). It was also demonstrated that once reduced, eukaryotic UGMs can complete an average of several hundred turnovers before oxidation/inactivation occurs.…”
Section: Covalent N5-iminium: Udp-galatopyranose Mutasementioning
confidence: 99%
See 1 more Smart Citation
“…However, it was later determined that UGM is only active when the flavin is in the reduced form (Zhang and Liu, 2000;Sanders et al, 2001;Goni et al, 2008;Oppenheimer et al, 2010Oppenheimer et al, , 2011Maaliki et al, 2020). Eukaryotic UGMs from A. fumigatus and the protozoa T. cruzi, L. Mexicana, and L. infantum utilize NADPH as a co-substrate and can both reinstate and stabilize the reduced form of the enzyme under aerobic conditions (Dhatwalia et al, 2012c;Oppenheimer et al, 2012;Fonseca et al, 2013). It was also demonstrated that once reduced, eukaryotic UGMs can complete an average of several hundred turnovers before oxidation/inactivation occurs.…”
Section: Covalent N5-iminium: Udp-galatopyranose Mutasementioning
confidence: 99%
“…It was also demonstrated that once reduced, eukaryotic UGMs can complete an average of several hundred turnovers before oxidation/inactivation occurs. This behavior occurs as a result of the rate of oxidation occurring 200 to 1500-fold slower than rate of re-reduction (Dhatwalia et al, 2012c;Fonseca et al, 2013;Tanner et al, 2014). Bacterial UGM can also utilize NADPH for enzyme reactivation but requires a large excess of NADPH and extended incubation times due to a 10,000-fold slower reduction rate compared to eukaryotic UGM, suggesting that alternative physiological reductants may be utilized by the bacterial forms in vivo (Barlow et al, 1999;Gusarov et al, 2008).…”
Section: Covalent N5-iminium: Udp-galatopyranose Mutasementioning
confidence: 99%
“…We have been working with eukaryotic UGMs (eUGM), which share low sequence identity to bUGMs (~ 15%) and are, on average, ~ 100- amino acid longer than bUGMs [3740]. The presence of a covalent flavin-N5-adduct was demonstrated in eUGMs [41] and the structures of the free enzyme and in complex with UDP-Gal p in the oxidized and reduced state have been elucidated [4245].…”
Section: Priming the Flavin-n5 For Reactivity In Non-redox Reactionsmentioning
confidence: 99%
“…91,92 Many studies have been devoted to the search for inhibitors of both families of enzymes, but more extensively in prokaryotes, including Klebsiella pneumoniae 93,94 and Mycobacterium tuberculosis. 91,92 Many studies have been devoted to the search for inhibitors of both families of enzymes, but more extensively in prokaryotes, including Klebsiella pneumoniae 93,94 and Mycobacterium tuberculosis.…”
Section: Udp-galp Mutase As a Potential Targetmentioning
confidence: 99%
“…Regarding Leishmania, UDP-Galp mutases from L. major, L. infantum and L. mexicana species have been produced very recently. 91,92 Many studies have been devoted to the search for inhibitors of both families of enzymes, but more extensively in prokaryotes, including Klebsiella pneumoniae 93,94 and Mycobacterium tuberculosis. [95][96][97][98][99] Unfortunately, sequence identity between the prokaryotic mutase from Aspergillus fumigatus 100 and eukaryotic ones, such as Leishmania, is very low (14-18%).…”
Section: Udp-galp Mutase As a Potential Targetmentioning
confidence: 99%